Cross-Reactivity of Virus-Specific CD8+ T Cells Against Allogeneic HLA-C: Possible Implications for Pregnancy Outcome - van der Zwan, Anita; van der Meer-Prins, Ellen M. W.; van Miert, Paula P. M. C.; van den Heuvel, Heleen; Anholts, Jacqueline D. H.; Roelen, Dave L.; Claas, Frans H. J.; Heidt, Sebastiaan (Frontiers in Immunology, 2018)
Heterologous immunity of virus-specific T cells poses a potential barrier to transplantation tolerance. Cross-reactivity to HLA-A and -B molecules has broadly been described, whereas responses to allo-HLA-C have remained ill defined. In contrast to the transplant setting, HLA-C is the only polymorphic HLA molecule expressed by extravillous trophoblasts at the maternal-fetal interface during pregnancy. Uncontrolled placental viral infections, accompanied by a pro-inflammatory milieu, can alter the activation status and stability of effector T cells. Potential cross-reactivity of maternal decidual virus-specific T cells to fetal allo-HLA-C may thereby have detrimental consequences for the success of pregnancy. To explore the presence of cross-reactivity to HLA-C and the other non-classical HLA antigens expressed by trophoblasts, HLA-A and -B-restricted CD8+ T cells specific for Epstein-Barr-virus, Cytomegalovirus, Varicella Zoster virus and Influenza virus were tested against target cells expressing HLA-C, -E and -G molecules. An HLA-B*08:01-restricted EBV-specific T cell clone displayed cross-reactivity against HLA-C*01:02. Furthermore, cross-reactivity of HLA-C-restricted virus-specific CD8+ T cells was observed for HCMV HLA-C*06:02/TRA CD8+ T cell lines and clones against HLA-C*03:02. Collectively, these results demonstrate that cross-reactivity against HLA-C can occur and thereby may affect pregnancy outcome.